PERAN TUTOR DALAM PROSES PERKEMBANGAN SOSIAL ANAK USIA DINI DI PLATGROUP ISLAM EL-AKHYAAR CITEUREUP - Amelia Putri; Musa, Safuri; Santika, Tika (Comm-Edu (Community Education Journal), 2025)
This study aims to describe the role of tutors, the impact, and the factors that influence early childhood social development. This playgroup is designed to be an appropriate environment for play, aiding in the growth and development of children, particularly in their social development. Harlock (1978), as cited in Khadijah and Jf (2021:12), states that "social development means the acquisition of the ability to behave in accordance with social demands." This research employs a case study method with a qualitative approach, involving interviews, observation, and documentation. The subjects of this study consisted of five respondents. Data analysis was carried out through a process of collection, presentation, reduction, and verification. The findings indicate that tutors play a crucial role as facilitators in guiding and training children to exhibit good social behaviors such as adaptation, interaction, tolerance, and responsibility. Additionally, tutors serve as role models, whose attitudes and actions significantly influence children's social development in their external environment. The most influential factors in children's social development are their internal emotional and intellectual factors. In conclusion, tutors at the El-Akhyaar Citeureup Islamic Playgroup have effectively fulfilled their roles in fostering good social behavior in children. However, it is recommended to build partnerships to implement programs that further support the process of children's growth and development.